Negro influences on Indonesia - Jeffreys, M. D. W. (International Library of African Music, 1961)
The Rev. A. M. Jones in a recent article* on the relationship between Indonesian and African music has called attention to a very interesting cultural feature, but his deductions that Negro African music is indebted to Indonesia is open to grave doubt. The similarities in music between Indonesia and Africa are due to the impress that African Negroes, imported into Melanesia by the Arab slave trade, exerted on the culture traits of Indonesia.
Keywords: Slave trade; Indian Ocean Region; Civilization; Culture diffusion; Ethnology; Indonesia; Melanesia; Arab Slave Trade; African Music